Does atraumatic restorative treatment reduce dental anxiety in children? A systematic review and meta-analysis - Simon, Arun K.; Bhumika, T. V.; Nair, N. Sreekumaran (European Journal of Dentistry, 2015)
Dental anxiety is one of the major problems affecting children, which impairs the rendering of dental care, leading to impaired quality of life. It often leads to occupational stress in dental personnel and conflict between parents/caregivers. The objective of this study was to conduct a systematic review and meta-analysis of randomized controlled trials done in children, to synthesize evidence of the effectiveness of atraumatic restorative treatment (ART) in reducing dental anxiety in children compared to conventional restorative treatments. The databases searched included PubMed, Google Scholar and The Cochrane Oral Health Group's Trials Register. Eligible studies reporting dental anxiety by a variety of psychometric scales were tabulated. The review was conducted and reported in accordance with the guidelines provided by the Cochrane Collaboration. Among 416 studies retrieved through literature search, six studies matched the inclusion criteria. Due to lack of data, only three studies were included for meta-analysis using RevMan software (Review Manager, Version 5.3;The Cochrane Collaboration, Copenhagen, 2014). The pooled meta-analysis data, (standardized mean difference − 2.12 [95% confidence interval: −4.52, 0.27]) failed to show any difference between ART group and the conventional treatment group. In conclusion, ART was not more beneficial in reducing dental anxiety among pediatric dental patients. The findings are relevant in the field of clinical practice in dentistry in the management of the anxious pediatric dental patient.
Keywords: Child; dental restoration; oral health; panic; practice guideline; test-anxiety scale